2018
DOI: 10.1002/mbo3.594
|View full text |Cite
|
Sign up to set email alerts
|

Coping with arsenic stress: Adaptations of arsenite‐oxidizing bacterial membrane lipids to increasing arsenic levels

Abstract: Elevated levels of arsenic (As) in aquifers of South East Asia have caused diverse health problems affecting millions of people who drink As‐rich groundwater and consume various contaminated agriculture products. The biogeochemical cycling and mobilization/immobilization of As from its mineral‐bound phase is controlled by pH, oxic/anoxic conditions, and different microbial processes. The increased As flux generated from ongoing biogeochemical processes in the subsurface in turn affects the in situ microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Acidovorax and Dechloromonas) have previously been observed in these wells. Moreover, recent cultured studies from BDP wells (204 and 28) have reported the presence of several strains of Acidovorax, many of which are potentially new species [12]. These results suggest that potential of Gallionellaceae in trapping arsenic indirectly through the production of biogenic iron oxides.…”
Section: Diversity Of Betaproteobacteria In the Bdp Aquifersmentioning
confidence: 85%
See 2 more Smart Citations
“…Acidovorax and Dechloromonas) have previously been observed in these wells. Moreover, recent cultured studies from BDP wells (204 and 28) have reported the presence of several strains of Acidovorax, many of which are potentially new species [12]. These results suggest that potential of Gallionellaceae in trapping arsenic indirectly through the production of biogenic iron oxides.…”
Section: Diversity Of Betaproteobacteria In the Bdp Aquifersmentioning
confidence: 85%
“…The specificity of the newly designed primers was investigated by targeting genomic DNA extracted from 3 Betaproteobacteria strains (Hydrogenophaga atypica strain BDP10, Hydrogenophaga bisanensis strain BDP20 and Acidovorax facilis strain BDP24) isolated previously in our laboratory from groundwater of our study site [12]. Successful amplification of a ca.…”
Section: Diversity Of Betaproteobacteria In the Bdp Aquifersmentioning
confidence: 99%
See 1 more Smart Citation
“…each can differ in how they are assembled in lymphocyte membrane bi-layers. Although we have not yet studied the potential impact of in utero As exposure on membrane fluidity, it is known that As-induced "stress" can cause changes in cell membrane fluidity (Ghosh et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…and Stenotrophomonas sp. are well known (Ben Fekih et al, 2018;Ghosh et al, 2018). Many studies revealed that microorganisms have evolved a variety of strategies to survive toxic effects of As compounds.…”
Section: Introductionmentioning
confidence: 99%